1995
DOI: 10.1111/j.1151-2916.1995.tb08670.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Segregation during Centrifugal Consolidation of Particulate Suspensions: Particle Drafting

Abstract: Dilute, dispersed, multicomponent suspensions containing Ce-ZrO,, AI,O,, and varying Al,O,-platelet contents were centrifugally consolidated. Despite the favorable conditions for segregation, phase and size segregation did not occur in the highest Al,O,-platelet content suspension. The suspension properties did not consist of agglomeration, high solids fractions, or high suspension viscosities typically attributed with segregation prevention. Thus, a new mechanism is suggested, considering the effects of hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…There is a need to prepare stabilized colloidal slurries containing sub-micrometer particles with high solids loadings, while still maintaining relatively low viscosities, to achieve a uniformly consolidated compact [6,7]. The fact that such slurry contains sub-micron particles with high solids loadings implies that many rheological problems are essentially related to the tendency to aggregate particles, which often gives rise to an inhomogeneous packing morphology.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need to prepare stabilized colloidal slurries containing sub-micrometer particles with high solids loadings, while still maintaining relatively low viscosities, to achieve a uniformly consolidated compact [6,7]. The fact that such slurry contains sub-micron particles with high solids loadings implies that many rheological problems are essentially related to the tendency to aggregate particles, which often gives rise to an inhomogeneous packing morphology.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, if very high concentrated slurries are used, the time for cast formation will be further delayed. Nevertheless, an increase in solid content is essential in many cases to avoid segregation specially in multicomponent slurries 17,18 . In addition, it is also reported that the more concentrated the initial slurry, the higher the packing density of the cast body 8,19 …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, an increase in solid content is essential in many cases to avoid segregation specially in multicomponent slurries. 17,18 In addition, it is also reported that the more concentrated the initial slurry, the higher the packing density of the cast body. 8,19 Use high centrifugal accelerations for processing highly concentrated slurries is an effective solution for a fast process without significant segregation of particles.…”
Section: Introductionmentioning
confidence: 99%